THE ROUTLEDGE INTERNATIONAL HANDBOOK OF MULTIDISCIPLINARY PERSPECTIVES ON CHARACTER DEVELOPMENT. Moderators, Threats, and Contexts - Matthews, Michael D.; Lerner, Richard M. (Routledge International Handbooks Series, 2024)
This volume explores the meaning, structure, function, and development of the construct of character virtues -- the attributes of thinking, feeling, and behavior that reflect an individual's positive and coherent contributions to self and, integratively, to the institutions of civil society, social well-being, equity, and social justice